2010 IEEE/RSJ International Conference on Intelligent Robots and Systems 2010
DOI: 10.1109/iros.2010.5649089
|View full text |Cite
|
Sign up to set email alerts
|

Robot motor skill coordination with EM-based Reinforcement Learning

Abstract: Abstract-We present an approach allowing a robot to acquire new motor skills by learning the couplings across motor control variables. The demonstrated skill is first encoded in a compact form through a modified version of Dynamic Movement Primitives (DMP) which encapsulates correlation information. Expectation-Maximization based Reinforcement Learning is then used to modulate the mixture of dynamical systems initialized from the user's demonstration. The approach is evaluated on a torque-controlled 7 DOFs Bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
187
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(189 citation statements)
references
References 24 publications
0
187
0
2
Order By: Relevance
“…Our novel algorithm, PoWER, is based on an expectation-maximization inspired optimization and a structured, state-dependent exploration. Our approach has already given rise to follow-up work in other contexts, for example, [Vlassis et al, 2009, Kormushev et al, 2010. Theodorou et al [2010] have shown that an algorithm very similar to PoWER can also be derived from a completely different perspective, that is, the path integral approach.…”
Section: Policy Learning By Weighting Exploration With the Returns (Pmentioning
confidence: 94%
See 1 more Smart Citation
“…Our novel algorithm, PoWER, is based on an expectation-maximization inspired optimization and a structured, state-dependent exploration. Our approach has already given rise to follow-up work in other contexts, for example, [Vlassis et al, 2009, Kormushev et al, 2010. Theodorou et al [2010] have shown that an algorithm very similar to PoWER can also be derived from a completely different perspective, that is, the path integral approach.…”
Section: Policy Learning By Weighting Exploration With the Returns (Pmentioning
confidence: 94%
“…Our approach has inspired follow-up work in other contexts, for example [Vlassis et al, 2009, Kormushev et al, 2010. Theodorou et al [2010] have derived algorithms based on the path integral approach that are very similar to PoWER and have also been successfully employed for robotic tasks [Buchli et al, 2011, Tamosiunaite et al, 2011.…”
Section: Policy Learning By Weighting Exploration With the Returns (Pmentioning
confidence: 99%
“…They have been used successfully to solve many complex tasks, including the 'Ball-in-the-Cup' game [4], Ball-Throwing [5], Pancake-Flipping [6] and bipedal gait generation [7]. The original motivation for using MPs is to compose complex behavior out of simpler building blocks of movement, or movement primitives.…”
Section: Introductionmentioning
confidence: 99%
“…Such representations use time-or phase-dependent policies [1], [6], [9]. For example, the widely used dynamic movement primitive (DMP) approach [1] uses a phase signal to implement execution speed adaptation for the movement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation